Linguodidactic opportunities of authentic texts in improving the sociolinguistic competence of future English language teachers (Eurasian Research Bulletin, 2025)
In the evolving landscape of global communication, the ability to navigate diverse sociolinguistic contexts is increasingly crucial for English language teachers. This article explores the linguodidactic potential of authentic texts in developing the sociolinguistic competence of future English language teachers. By analyzing the nature of authentic materials and their pedagogical applications, the article highlights how these resources contribute to a deeper cultural awareness, pragmatic usage, and contextual language understanding. The study also proposes methodological strategies for integrating authentic texts into teacher education and discusses challenges and considerations for their effective use. Ultimately, the article aims to emphasize the role of authenticity in preparing educators who are linguistically competent, culturally sensitive, and pedagogically equipped to facilitate meaningful language learning